Optimizing Infrastructure, Public Information, and Environmental Awareness Through a Community Service Program in Bangelan Village - Rakha Virlo Ramadhan; Zulvania Fahira Rahmadani; Dwi Putri Isnaini Mayumi; Ananda Ayu Maulidan Nabila; Chindy Bella Sasmita; Frendy Aru Fantiro (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Kuliah Kerja Nyata (KKN), or Community Service Program, is a form of community engagement that allows university students to apply their knowledge and skills to address real-world community issues. This KKN program was carried out in Bangelan Village, Wonosari Subdistrict, Malang Regency a village covering approximately 768.10 hectares comprising four hamlets (Bangelan, Arjomulyo, Sidomulyo, and Kampung Baru), and officially designated as a Tourism Village since 2023. The program focused on strengthening public facilities, improving regional information, enhancing road safety, and promoting environmental awareness.Field observations identified the need for signage marking irrigation and waste facilities, street name identification, improved visibility of roads and bridges, and informational signs on restrictions in water source and river areas. The main programs included the construction of irrigation and waste signage, street name signs for Kampung Baru, installation of road reflectors, and repainting of Taman Bridge, supported by additional programs such as prohibition signs at Umbulan Spring and river restriction signs.The program was implemented through a participatory approach involving observation, coordination, design, production, installation, and evaluation. The results included the installation of 8 irrigation signs, 11 street name signs for Kampung Baru, 2 prohibition signs at Umbulan Spring, 2 river restriction signs, reflective markings at one road point, and the repainting of Taman Bridge helping the community identify facility functions, regional identity, and environmental usage rules, while also improving the visibility of roads and bridges.